Optimalisasi Pendistribusian Susu Nasional dengan Menggunakan Metode Assignment (Hungarian) dan Metode Networking Spanning Tree - Indah Purnama Sari; Rianita Puspa Sari; Wahyudin Wahyudin; Ida Rinjani (Fakultas Teknik, 2021)
The problems at the National Dairy Depot are sales productivity problems, regarding the assignment of workers, as well as regarding the distribution allocation network in Teluk Jambe Timur District, which consists of nine workers. The purpose of this research is to optimize the distance and time in the distribution of National Milk. The method used in the assignment of workers is the Assignment (Hungarian) method, and to optimize the distribution network allocation of milk by using the Networking (Spanning Tree) method. Using these two methods, the optimum total allocation of products sold is 1350 pieces of national milk, and the minimum distance that must be traveled by workers in distributing national milk is 39.18 Km.